OS FATORES QUE INFLUENCIAM NO CLIMA ORGANIZACIONAL EM INSTITUIÇÕES FEDERAIS DE ENSINO SUPERIOR: UMA INVESTIGAÇÃO EM BELÉM DO PARÁ, BRASIL - Carlos André Corrêa de Mattos (Universidade Federal de Santa Catarina, 2019)
The organizational environment can be conceptualized as the product of perception shared by workers about the work environment quality at one point. Over time, organizational climate studies show human behavior relationships under many aspects as motivation, productivity, commitment, among others. In this way, understanding the organizational climate has become a privileged way to investigate the work environment. In this context, the objective of this study was to analyze some work environment aspects that affect the formation of the organizational climate in federal educational institutions. The research used an exploratory and descriptive method under form of field research in two institutions of Belém City, Pará State, Brazil. Sampling was non-probabilistic by accessibility, performing 236 valid interviews. Data treatment was quantitative with exploratory factorial analysis (EFA) and multiple linear regression (MLR). The factor analysis caught four factors that explained 65.25% of the data variance and were denominated as Management (18.97%), Organizational Image (17.57%), Training (17.41%), and Compensation (11.30 %). With r-squared of 70.81%, the multiple linear regression showed that the model was capable to strongly influencing the organizational climate. It is concluded that managers can use the factors identified by this study to support strategies that contribute to improvement of the organizational climate in the researched institutions.